An outbreak of food-borne gastroenteritis in two hospitals associated with a Norwalk-like virus. - Pether, J. V. (Cambridge University Press, 1983)
Two connected outbreaks of gastroenteritis in separate hospitals associated with a small round structured virus morphologically indistinguishable from the Norwalk virus are described. The virus was most probably introduced on chicken sandwiches prepared by a member of the kitchen staff who was incubating the disease.